Dampak Penggunaan Gadget dengan Perkembangan Emosional Pada Anak Usia Prasekolah - Marlin Sutrisna; Ravika Ramlis; Elsi Rahmadani (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
Excessive use of gadgets can interfere with child development, especially in preschoolers. The purpose of this study was to determine the correlation between gadget use and emotional development of preschool children at Bentiring Bengkulu Health Center. The method used is an analytical research design with a cross sectional approach. The sample in this study were mothers who had preschool children as many as 63 preschool children using accidental sampling technique. This study uses SPSS with a chi-square bivariate statistical test with a value of =<0.05. The results of the univariate analysis showed that almost half of the respondents 49.2% or 31 respondents had moderate use of gadgets, and more than half of the respondents 61.9% or 39 respondents had normal emotional development. The results of the bivariate analysis showed that there was a correlation between the use of gadgets and the emotional development of preschool children (p = 0.003). The conclusion is that there is a relationship between the use of gadgets and the emotional development of preschool children at Bentiring Bengkulu. The researcher suggests the health center should be more active in conducting counseling or education about child development and the effects of using gadgets on children on a regular basis